Our ghosts were once people : stories on death and dying - Kona, Bongani (Johannesburg ; Cape Town : Jonathan Ball Publishers, 2021)
"This poignant and thought-provoking anthology gives us portraits of grief as seen through the eyes of writers and poets such as Sisonke Msimang, Dawn Garisch, Lidudumalingani, Mary Watson, Ishtiyaq Shukri, Hedley Twidle, Karin Schimke, Khadija Patel, Shubnum Khan and many others. The contributions range from the deeply personal: a poet chronicles her relationship with her troubled, abusive father, a World War II survivor - to the political: an investigator from the Missing Persons Task Team draws us into the ongoing search for the remains of activists who were murdered by the apartheid state between 1960 and 1994 - to the philosophical: a writer ponders the ethics of killing small animals. Perhaps grief never truly ends but these stories transform the pain of death into something beautiful so that we can find ways to live with loss."--Provided by publisher.
"Originally published in South Africa in 2021 by Jonathan Ball Publishers."
Keywords: Grief; Death; Loss (Psychology); Bereavement -- Psychological aspects